SOIL AS MATERIAL FOR THE CREATION OF HUMANS, PERSPECTIVES FROM THE HOLY QURAN AND SCIENCE - Dirhamzah, Dirhamzah; Amrullah, Syarif Hidayat (Universitas Islam Negeri Alauddin Makassar, 2022)
Research in this paper discusses soil as a material for human creation using the method of literature study (library research). As the results found that humans were created from the soil, in the sense that all humans are sourced from the basic material of wet soil (Thiin), then Adam as the first man created from dry soil (Turab) which is a soil that has undergone processes and stages of change, from Thiin, to Min Thiin Lazibin (Clay), to Shalshalin Min Hammain Masnun (clay from black mud), became Shalsalin Kalfahar (dry clay like pottery), then became Turab (dust soil dust/loose soil). While humans are generally created through a biological process that is the meeting between male sperm and female ovum, where the sperm comes from the soil essence (Sulalaten min Thiin). The creation of man from the soil has been justified by the discovery of science that the chemical elements present in the soil are the same as the chemical elements in the human body, namely in the form of iron (Fe), copper (Cu), cobalt (Co), manganese (Mn), and so on. With the addition of the elements carbon (C), hydrogen (H), nitrogen (N), and oxygen (O).